Contemplating Maternity in an Era of Choice: Explorations into Discourses of Reproduction - Hayden, Sara; O'Brien Hallstein, Lynn (Lexington Books, 2010)
Women who came of age in the late twentieth century were raised in the era of choice; they grew up believing that reproductive decision-making is a political right, a responsibility of women living the successes of second wave feminism, and under their control. Contemplating Maternity in an Era of Choice: Explorations into Discourses of Reproduction explores contemporary maternity both within and in light of these late-twentieth century understandings. Employing a variety of feminist communication approaches, the volume's contributors discuss how discourses of choice shape and are shaped by women's identities and experiences as (non)mothers and how those same discourses affect and reflect private practices and public policies related to reproduction and motherhood. Through this process, the contributors illustrate a variety of ways of conducting feminist thinking, research, and practices within the communication discipline. Major sub-disciplines within communication studies are represented here including feminist organizational, interpersonal, rhetorical, critical/cultural, and social movement studies. Whereas many of the previous scholarly investigations into maternity highlight only one aspect or phase of motherhood, Contemplating Maternity in an Era of Choice is unique because it investigates discourses of choice across the arc of maternity and as enacted through various (non)maternal subject positions.